Penerapan Mata Kuliah Praktik Kewirausahaan terhadap Motivasi Mahasiswa Akuntansi dalam Membentuk Karakter Entrepreneurship - Tri Septiana Wati; Hartono Hartono; Tatas Ridho Nugroho; M. Bahril Ilmiddaviq (Jurnal Kendali Akuntansi, 2023)
Indonesia is one of the most densely populated countries in the world. As a country with the largest population, it means that the government must prepare jobs. Along with the increasing population and changes in the era of industrialization, Indonesia is experiencing problems, namely the depletion of jobs with an increase in the number of job seekers, most of whom are university graduates, causing unemployment. This condition certainly threatens university graduates who are in the productive age group and are focused on becoming a workforce. Preparing graduates who are adaptive and capable of opening jobs needs to be given more attention at this time. This research aims to. This study aims to understand the conditions of learning and entrepreneurial activities at Islamic University of Majapahit. The method used in this research is qualitative method. Data collection techniques used in this study were interviews, observation, and documentation. This study produced a description of the learning conditions which were divided into three discussions, namely, learning systems, learning processes, and entrepreneurial activities with found to be a lack of educational capacity to form graduates with entrepreneurial profiles. These results can be a reference for other tertiary institutions in finding solutions by mapping the problems that occur. Other contributions of this research complement previous research related to entrepreneurship.